2020
DOI: 10.3390/rs12182984
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the Performance of Several Gridded Precipitation Products over the Highland Region of Yemen for Water Resources Management

Abstract: Management of water resources under climate change is one of the most challenging tasks in many arid and semiarid regions. A major challenge in countries, such as Yemen, is the lack of sufficient and long-term climate data required to drive hydrological models for better management of water resources. In this study, we evaluated the accuracy of accessible satellite and reanalysis-based precipitation products against observed data from Al Mahwit governorate (highland region, Yemen) during 1998–2007. Here, we ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Although a comprehensive assessment of the impacts of LULCC on summer rainfall amount and extremes was conducted in this study, some issues remained. For example, only one regional climate model (i.e., the WRF model) was used in this study, although it has been widely used in China (Huang et al, 2020;Azmat et al, 2020). Some previous studies indicated that results from a single RCM (regional climate model) had a significant uncertainty since RCMs could perform differently in the same region (Davin et al, 2020;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although a comprehensive assessment of the impacts of LULCC on summer rainfall amount and extremes was conducted in this study, some issues remained. For example, only one regional climate model (i.e., the WRF model) was used in this study, although it has been widely used in China (Huang et al, 2020;Azmat et al, 2020). Some previous studies indicated that results from a single RCM (regional climate model) had a significant uncertainty since RCMs could perform differently in the same region (Davin et al, 2020;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they may be useful in observationscarce regions. However, it seems that over arid regions reanalysisbased rain fields are inferior compared to other regions (Beck et al, 2017), and were found to not represent well rainfall variability e.g., in the arid and semi-arid highlands of Yemen (Al-Falahi et al, 2020), nor local-scale high-intensity rainfall in the eastern Mediterranean deserts (Armon et al, 2020;Rinat et al, 2021). Indeed, without the explicit representation of convective processes, model-based rainfall cannot be expected to represent precipitation with high reliability, even if the larger-scale meteorological environment is well-represented (e.g.…”
Section: Rainfall Observations In the Saharamentioning
confidence: 95%
“…The lack of climate-related data is a significant challenge in Yemen to reach hydrological models that represent reality and seek better manage water resources [25]. The climate change phenomenon is one of the most important topics that should receive significant attention due to its relationship with natural resources.…”
Section: Rainfallmentioning
confidence: 99%